Pulsational instabilities in hot pre-horizontal branch stars - Battich, Tiara (2017)
The ϵ mechanism is a self-excitation mechanism of pulsations which acts on the regions where nuclear burning takes place. It has been shown that the ϵ mechanism can excite pulsations in models of hot helium-core flash, and that the pulsations of LS IV-14° 116, a He-enriched hot subdwarf star, could be explained that way. We aim to study the ϵ mechanism effects on models of hot pre-horizontal branch stars and determine, if possible, a domain of instability in the log g - log Teff plane. We compute non-adiabatic non-radial pulsations on such stellar models, adopting different values of initial chemical abundances and mass of the hydrogen envelope at the time of the main helium flash. We find an instability domain of long-period (400 s ≤ P ≤ 2500 s) g-modes for models with 22000K ≤ Teff ≤ 50000K and 4.67 ≤ log g ≤ 6.15.